IoT-Based Barcode Scanning System for Production and Warehouse Management - Ivan De Nerol; Riyo Putra Syam Satria; Rafi Rasyid Parmana; Nanda Octavia; Muhammad Danang Mukti Darmawan; Mohamad Mohamad Alvin Renaldi; Firdayanti; Fiqri Nurfadillah; Fiona Kharismatunnisaa; Ester Angeline; Dhafa Kamil; Yourdan Saputra (Batrisya Education, 2024)
This project aims to develop an IoT-based barcode scanning system using an ESP32 microcontroller and a GM-65 barcode reader for efficient production and warehouse management. The system facilitates automated and accurate barcode scanning, with the collected data transmitted to a web-based platform in real-time. The web interface provides users with comprehensive insights into production quantities and warehouse status, generating a detailed journal for traceability and accountability. This innovative solution offers businesses a streamlined approach to monitor and record production activities, ultimately optimizing the overall efficiency of production and warehouse management processes.